Pseudoseptic Arthritis: A Case Series and Review of the Literature. (13th October 2011) - Oppermann, Brian P.; Cote, Jonida K.; Morris, Stephanie J.; Harrington, Thomas
Abstract : Purpose . Pseudoseptic arthritis is an acute inflammatory monoarthritis with a sterile synovial gram stain and culture. Pseudoseptic arthritis has been previously described in the literature in a variety of settings including rheumatoid arthritis and microcrystalline disease. Despite pseudoseptic arthritis being a described entity, there is little published data on this topic with no published reports since 1992. Methods . This paper was a retrospective chart review over a 20-year period that identified all rheumatology inpatient consultations at our tertiary rural hospital for pseudoseptic arthritis. Results . We identified 10 patients with pseudoseptic arthritis and presented 5 of those cases in this paper. Majority of these patients had known autoimmune inflammatory arthritis or microcrystalline inflammatory arthritis. Conclusion . Pseudoseptic arthritis is a syndrome that should be in the differential diagnosis with patients with long standing inflammatory condition who present with an acute monoarthritis with no known bacterial source for septic arthritis.